From Amsterdam to Berbice; Colonial administrative buildings as new design commissions for Abraham van der Hart (Bulletin KNOB, 2008)
During the years when Abraham van der Hart, as town architect of Amsterdam, worked among other things on the design and construction of the workhouse Nieuwe Werkhuis, he was also involved in various other large projects. In Amsterdam he designed the Roman-Catholic girls' orphanage on Spui, the Maagdenhuis. In the same period he was asked to give advice on a design for a new government building in Berbice, a Dutch colony in South America, governed by the Society of Berbice.Van der Hart did not only give advice on this design for a complex of buildings with four wings around an open inner courtyard, but he also drew a new design himself. Starting from the various functions (government, residence for the governor, barracks, hospital) he designed an ambitious project that was to consist of six separate buildings. The board of directors of the Society of Berbice was immediately impressed by it, and Van der Hart was asked to make two sets of drawings, so that one set could also be forwarded to the colony. Later, indecisiveness and fear to invest in the colony caused a delay, and when British troops captured the colony in 1781, the construction of the new government buildings was put off.Eventually, the design was never realized. It is a fascinating project in the oeuvre of Van der Hart. In architectonic design the complex of buildings for the government of Berbice is to be compared to the Nieuwe Werkhuis and the Maagdenhuis in Amsterdam, but the functions and location in a West Indian colony make the design a striking exception in the long career of Van der Han. It is evident from the quick and well-considered way in which Van der Hart was able to design three large projects in the same period - two of which were actually realized - that even before his appointment as town architect of Amsterdam in 1777 he must have had a distinct reputation, based on thorough architectonic knowledge and experience in the building practice.